Circumferential Liposuction of the Thigh with Concomitant Fat Transplantation to the Infragluteal Region: A Promising Option for Preventing Postliposuction Gluteal Ptosis. Issue 1 (6th May 2022) - Gu, Yunpeng; Yang, Mingzi; Sun, Jingjing; Lv, Qianwen; Qi, Yue; Jin, Ji; Liu, Zhenjun; Qi, Zuoliang; Ma, Gui-e
Abstract : Background: Gluteal ptosis is a common complication of circumferential liposuction of the thigh. The authors propose a novel concept of combining circumferential liposuction of the thigh with concomitant fat transplantation to the infragluteal/posterior thigh junction region to prevent postliposuction gluteal ptosis. Methods: Patients underwent circumferential liposuction of the thigh with or without concomitant fat transplantation from 2015 to 2020 and were retrospectively reviewed. The postoperative changes in the grade of gluteal ptosis, length of hospitalization, time to recovery, postoperative complications, and patient satisfaction were evaluated. Results: A total of 109 patients were enrolled in this study, including 46 patients in the liposuction-only group and 63 patients in the liposuction plus fat transplantation group. There was no significant difference in fat removal volume between the liposuction-only group and the liposuction plus fat transplantation group ( p = 0.152). Aggravation of gluteal ptosis occurred in 43 patients (93.5 percent) in the liposuction-only group and four patients (6.3 percent) in the liposuction plus fat transplantation group ( p < 0.001). The length of hospitalization and time to recovery was not significantly different between the two groups ( p = 0.402 and p = 0.423, respectively). Complications were rare in both groups. With a minimum evaluation time of 6 months, patients in the liposuction plus fat transplantation group showed significantly higher satisfaction ( p < 0.001). Conclusion: Concomitant fat transplantation to the infragluteal/posterior thigh junction region during circumferential liposuction of the thigh is effective in preventing postliposuction gluteal ptosis and improving patient satisfaction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.